Overexpression of GhWRKY27a reduces tolerance to drought stress and resistance to Rhizoctonia solani infection in transgenic Nicotiana benthamiana - Yan, Yan; Jia, Haihong; Wang, Fang; Wang, Chen; Liu, Shuchang; Guo, Xingqi (Frontiers in Physiology, 2015)
WRKY proteins constitute transcriptional regulators involved in various biological processes, especially in coping with diverse biotic and abiotic stresses. However, in contrast to other well-characterized WRKY groups, the functions of group III WRKY transcription factors are poorly understood in the economically important crop cotton (Gossypium hirsutum). In this study, a group III WRKY gene from cotton, GhWRKY27a, was isolated and characterized. Our data indicated that GhWRKY27a localized to the nucleus and that GhWRKY27a expression could be strongly induced by abiotic stresses, pathogen infection, and multiple defense-related signaling molecules. Virus-induced gene silencing (VIGS) of GhWRKY27a enhanced tolerance to drought stress in cotton. In contrast, GhWRKY27a overexpression in Nicotiana benthamiana markedly reduced plant tolerance to drought stress, as determined through physiological analyses of leaf water loss, survival rates and the stomatal aperture. This susceptibility was coupled with reduced stomatal closure in response to abscisic acid and decreased expression of stress-related genes. In addition, GhWRKY27a-overexpressing plants exhibited reduced resistance to Rhizoctonia solani infection, mainly demonstrated by the transgenic lines exhibiting more severe disease symptoms, accompanied by attenuated expression of defense-related genes in Nicotiana benthamiana. Taken together, these findings indicated that GhWRKY27a functions in negative responses to drought tolerance and in resistance to Rhizoctonia solani infection.